Creating the Ideal Community as A Root of Fethullah Gulenâ€™s View on Gender Equality - Khamami, Akhmad Rizqon (AL-TAHRIR, 2019)
Abstract: This article discusses the roots of Gulen's view on gender equality and its roles within the movement, which constitutes an example of an Islamic movement that can adapt in the contemporary era and becomes progressive Islam. Conversely, Gulenâ€™s view on gender belongs to the conservative movement. By employing functionalism, this article tries to seek and delve into the theme. It further argues that the movements' mission to create â€œthe ideal communityâ€ is the driving ideology on gender relations. Examining some important scholarly findings on the movement and works by its founder Fethullah Gulen, the womenâ€™s position is unequally subordinated to that of men, as their initial functions to obey their husbands and to maintain familyâ€™s honor. Importantly, their role is limited to educate their children to deliver "the next golden generationâ€. Thus, it is reasonably true that Gulenâ€™s view on womenâ€™s rights and gender relations is envisioned along with the movement's mission to transform the society towards the ideal community that in turn sacrifices womenâ€™s freedom and liberty.Ø§Ù„Ù…Ù„Ø®Øµ: ÙŠÙ†Ø§Ù‚Ø´ Ù‡Ø°Ø§ Ø§Ù„Ù…Ù‚Ø§Ù„ Ø£ÙÙƒØ§Ø± ÙƒÙˆÙ„Ù† ØÙˆÙ„ Ø§Ù„Ø¹Ù„Ø§Ù‚Ø§Øª Ø¨ÙŠÙ† Ø§Ù„Ø¬Ù†Ø³ÙŠÙ†. Ø§Ù„Ø³Ø¤Ø§Ù„ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù…Ù‚Ø§Ù„ ØŒ Ù…Ø§ Ù‡ÙŠ Ø¬Ø°ÙˆØ± Ø§Ù„ÙÙƒØ±Ø© Ø¨ÙŠÙ† Ø§Ù„Ø¬Ù†Ø³ÙŠÙ† Ø¹Ù†Ø¯ ÙƒÙˆÙ„Ù†ØŸ ÙŠÙØªØ±Ø¶ Ø§Ù„Ù…Ø¤Ù„Ù Ø£Ù† ÙÙƒØ±Ø© ÙƒÙˆÙ„Ù† ØªÙ… ØªØ·ÙˆÙŠØ±Ù‡Ø§ Ù…Ù† Ø·Ù…ÙˆØØ§Øª ÙƒÙˆÙ„Ù† Ù„Ø¥Ù†Ø´Ø§Ø¡ Ù…Ø¬ØªÙ…Ø¹ Ù…Ø«Ø§Ù„ÙŠ. Ø£Ù†Ø·Ù„Ø§Ù‚Ø§ Ù…Ù†Ù‡Ø§ØŒ ÙŠØªÙ… Ø¥Ø¹Ø·Ø§Ø¡ Ø§Ù„Ù…Ø±Ø£Ø© ÙˆØ¸ÙŠÙØ© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø£Ø·ÙØ§Ù„ ØŒ ÙˆØ·Ø§Ø¹Ø© Ù„Ø²ÙˆØ¬Ù‡Ø§ ØŒ ÙˆØ§Ù„ØÙØ§Ø¸ Ø¹Ù„Ù‰ Ø§Ù„Ø´Ø±Ù ØŒ ÙˆØªÙƒÙˆÙ† Ø¹Ù„Ù‰ Ø§Ø³ØªØ¹Ø¯Ø§Ø¯ Ù„ØªÙƒÙˆÙ† ØªØ§Ø¨Ø¹Ø© Ù„Ù„Ø±Ø¬Ø§Ù„ ÙÙŠ Ø§Ù„Ø£Ø³Ø±Ø© ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹. ÙŠØ¶Ø¹ ÙƒÙˆÙ„Ù† Ø§Ù„Ù†Ø³Ø§Ø¡ ÙƒØ£ÙˆÙ„ Ù…Ø¹Ù„Ù…Ø§Øª Ù„Ø£Ø·ÙØ§Ù„Ù‡Ù†Ù‘ ÙˆØªÙ… ØªÙƒÙ„ÙŠÙÙ‡Ù† Ø¨ØªØ±Ø¨ÙŠØªÙ‡Ù… Ù„ÙŠÙƒÙˆÙ†ÙˆØ§ Ø¬ÙŠÙ„Ø§ Ø°Ù‡Ø¨ÙŠÙ‘Ø§ ÙÙŠÂ  Ø§Ù„Ù…Ø³ØªÙ‚Ø¨Ù„. Ø£Ø¹Ø±Ø¨ ÙƒÙˆÙ„Ù† Ø¹Ù† ØÙ‚ÙˆÙ‚ Ø§Ù„Ù…Ø±Ø£Ø© ÙˆØ§Ù„Ø¹Ù„Ø§Ù‚Ø§Øª Ø¨ÙŠÙ† Ø§Ù„Ø¬Ù†Ø³ÙŠÙ† Ù…Ù† Ø£Ø¬Ù„ Ø§Ù„ØªØÙˆÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ø¥Ù„Ù‰ Ù…Ø¬ØªÙ…Ø¹ Ù…Ø«Ø§Ù„ÙŠ. ÙˆÙ…Ù† Ø£Ø¬Ù„ ØªÙƒÙˆÙŠÙ† Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…Ø«Ø§Ù„ÙŠ ÙØªÙƒØ§Ù„ÙŠÙÙ‡ Ù‡ÙŠ ØªØ®Ø¶Ø¹ Ø§Ù„Ù†Ø³Ø§Ø¡ ØªØØª Ø§Ù„Ø±Ø¬Ø§Ù„.Abstrak: Artikel ini mengupas akar pemikiran Gulen tentang persamaan gender dan peran perempuan di tengah-tengah gerakan Gulen. Sejauh ini gerakan Gulen merupakan sebuah contoh gerakan Islam yang mampu beradaptasi dengan perkembangan dunia kontemporer dan dianggap sebagai gerakan Islam progresif. Akan tetapi, pandangan Gulen tentang gender justru merefleksikan warna konservatif. Dengan menggunakan pendekatan fungsionalisme, artikel ini berupaya menggali dan mengupas persoalan akademik tersebut. Artikel ini mengungkapkan bahwa misi gerakan Gulen dalam menciptakan â€œmasyarakat idealâ€ merupakan ideologi pendorong atas warna pandangan Gulen tentang hubungan gender dan peran perempuan. Sejumlah temuan tentang gerakan dan dari karya-karya Gulen mengungkapkan bahwa di mata Gulen posisi perempuan berada di bawah laki-laki dengan fungsi untuk mematuhi suami dan menjaga kehormatan keluarga. Peran perempuan dibatasi pada mendidik anak-anak mereka agar menjadi â€œgenerasi emasâ€. Karena itu, pandangan Gulen tentang relasi gender dan hak perempuan memperoleh bentuk senada dengan misi gerakan ini yang ingin mengubah masyarakat menjadi sebuah masyarakat ideal meskipun pada gilirannya harus mengorbankan kebebasan perempuan.